2020
DOI: 10.1186/s41938-020-00270-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of beneficial fungi in managing diseases and insect pests of tea plantation

Abstract: The effectiveness of Trichoderma atroviride, T. asperellum, T. harzianum, against targeted tea disease causing pathogen, Fusarium solani (dieback), Beauveria bassiana against tea mosquito (Helopeltis theivora), and Metarhizium anisopliae against the red spider mite, Oligonychus coffeae Nietner, and the live wood eating termite (Microcerotermes beesoni Snyder), respectively were evaluated under laboratory and field conditions. The Trichoderma isolates showed effective control of F. solani (64.6 to 71.7%) under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…This indicates that the adhesion of EPF spores over TMB is very high in the dipping process and adhesion spores will germinate, penetrate to the haemocoel then rapidly cause insect mortality (Ghaffari et al, 2017;Aw & Hue , 2017). Kumhar et al (2020) reported that the mortality was significantly dependent on spore concentration. A similar observation was made in the present study too.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the adhesion of EPF spores over TMB is very high in the dipping process and adhesion spores will germinate, penetrate to the haemocoel then rapidly cause insect mortality (Ghaffari et al, 2017;Aw & Hue , 2017). Kumhar et al (2020) reported that the mortality was significantly dependent on spore concentration. A similar observation was made in the present study too.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Beauveria (especially, Beauveria bassiana) have the ability to colonize multiple plant hosts without causing any apparent disease or showing secondary symptoms, yet retaining the capacity to infect insects and invoke induced systemic resistance (Wei et al 2020). A eld trial in Northeast India has reported Beauveria bassiana to be effective against Helopeltis theivora (a sucking pest of tea-leaves) and other tea pests (Borkakati and Saikia 2019; Kumhar et al 2020). Another entomopathogenic fungus Metarhizium (especially, M. anisopliae) is also regularly used as a broad spectrum insect biopesticide (Singha et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that Trichoderma WP formulation controlled the dieback disease of tea to a great extent when sprayed at 2.5 and 5.0 g/liter concentration and performed better than the commercial formulation of the antagonist. Light pruned (LP) and deep skipped (DS) tea bushes showed enhanced vegetative growth as compared to control [16]. Foliar spray of T. harzianum and T. viride on wheat crop managed head blight disease caused by Fusarium graminearum under greenhouse conditions better than control [17].…”
Section: Discussionmentioning
confidence: 99%